Analysis of sociodemographic, sport and psychological profile in a rock-climbing experience on university students - Pablo Morilla Portela; Socorro Rebollo Rico (FEADEF, 2013)
The relationships among several psychological factors in rock climbing was proved a long time ago, nevertheless, most researches are limited to very artificial situations, far away from nature. There are few studies which have carried out this kind of investigation in the natural environment and have combined data collection with real rock climbing practice. The instruments used for this data collection were two questionnaires: CSAI-2 and another one specifically designed to gather the necessary information about sociodemographic characteristic and sport habits. In our work we have studied various individuals' features (sociodemographic, general sport and outdoor profiles) and we have confirmed how they are interrelated and their influence on several psychological factors (cognitive anxiety, somatic anxiety and self-confidence). Through this article we show that there are higher percentages of women than men participants who climb IV-V grade, whereas in higher grades the percentages equalize. Regarding psychological factors, we can notice how on the one hand those participants who climb higher grades and are more interested in rock climbing, feel lower cognitive anxiety and somatic anxiety, while on the other hand they feel higher self-confidence levels